Edutraining Koperasi Pada KPRI “Nasib” Kecamatan Butuh Kabupaten Purworejo - Supriono, Supriono; Widiyohening, Caecilia Rosma; Ayuningtyas, Pratika (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2023)
Cooperatives are business entities that aim to improve the welfare of their members. KPRI "NASIB" is one of the cooperatives in Purworejo district whose members are civil servants, especially teachers and education staff. KPRI "NASIB" has problems reporting periodic financial reports due to the large number of managers who do not understand financial reports and there are no periodic structured financial reports. Edutraining, or education and training, is an effort to improve the ability of cooperative management so that financial reports are no longer an obstacle. Edutraining was held for two days from November 15–16, 2022 with 30 participants from various schools in the Need district. After its implementation, most of the administrators have understood the concept of financial reports, wherein they are expected to be able to prepare periodic financial reports according to existing standards